2017
DOI: 10.1186/s12960-017-0232-1
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of health care resources in Mongolia using the Gini coefficient

Abstract: BackgroundAttaining the perfect balance of health care resources is probably impracticable; however, it is possible to achieve improvements in the distribution of these resources. In terms of the distribution of health resources, equal access to these resources would make health services available to all people. The aim of this study was to compare the distributions of health care resources in urban, suburban, and rural areas of Mongolia.MethodsWe compared urban and rural areas using the Mann–Whitney U test an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
35
1
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(41 citation statements)
references
References 13 publications
3
35
1
2
Order By: Relevance
“…These studies show that many different countries suffer from the inequities in distribution of healthcare human resources [51]. Also, these studies indicated that country-specific lifestyle and culture should be taken into account when analysing equity in the distribution and formulation of healthcare human resources strategies.…”
Section: Theory Background and Literature Reviewmentioning
confidence: 83%
See 3 more Smart Citations
“…These studies show that many different countries suffer from the inequities in distribution of healthcare human resources [51]. Also, these studies indicated that country-specific lifestyle and culture should be taken into account when analysing equity in the distribution and formulation of healthcare human resources strategies.…”
Section: Theory Background and Literature Reviewmentioning
confidence: 83%
“…In order to examine the distribution of healthcare resources against population size and geographic size in Poland, the Gini coefficient calculated based on the Lorenz Curve was engaged, because it is recognized as one of the most common measure of distribution and also as one of the superior tools for measuring inequity [44][45][46][48][49][50][51][52][53][54][55][57][58][59][60][61][62][63][64][65]108,109]. The Gini coefficient was developed by the Italian Statistician Corrado Gini [110] as a summary measure of income inequality in society [111].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Various indices such as Gini Coe cient, Atkinson Index and Theil Index (21)(22)(23) are used to measure the equality in access to health services. Gini coe cient is more commonly used in health studies among different countries (24)(25)(26)(27)(28)(29)(30), which is de ned by Lorenz Curve. This index was designed by the Italian statistician and sociologist, Corrado Gini, and was initially used to measure inequality and distribution of wealth and income among population (31).…”
Section: Introductionmentioning
confidence: 99%